The relationship between financial support, non-financial attributes and entrepreneurial business performance: A case study on MARA SPiM loan scheme - Subhan, Muhammad; Hussain, Fawad; Md Isa, Mohd Azwardi; Ahmad Shukri, Saiful Husni (2016)
This paper is aimed at examining the relationship between financial support, non-financial attributes, and entrepreneurial business performance.The paper studied on how advisory services, entrepreneurial skills/knowledge, entrepreneurial mindset entrepreneurial attitude play a significant role in influencing business performance (profitability, growth and assets).Using a quantitative approach, this study analyzed data from 96 respondents from the survey of 105 participants.All respondents are entrepreneurs who were loan takers of MARA-SPiM scheme which was approved from 2014 to 2015 from 10 districts in Perak State of Malaysia.The analysis was performed using SPSS and Smart-PLS statistical software.The findings established that financial services play a significant role in influencing entrepreneur's business performance.On the other hand, it was revealed that entrepreneurial attitude (one of the non-financial attributes) plays a significant role in influencing entrepreneur's business performance.This study also found that the arrangement of financial services and non-financial services are very important for entrepreneurs' business success in term of rising profitability, growing their business and increasing their assets.Besides that, advisory services, entrepreneur skill/knowledge, and entrepreneur mindset were unable to show any influence on entrepreneurs' business performance.